Historical consciousness as a public discourse : an analysis of Malaysian experience - Mohd Adib Akmal Ahmad Shatir,; Shazlin Amir Hamzah, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Historical consciousness refers to one’s ability to apply historical knowledge in life. In a social context, a society with historical consciousness will always take into account past experiences as a guide to deal with one another. This condition however does not exist naturally. Aside from nurturing ‘the concern for history’, a set of data should be available as a guideline for the public. Data organized as discourses will guide an individual or society through the initial historical consciousness process. This article attempts to conceptually highlight the process of empowering historical consciousness in Malaysia. The focus will be on surveys of discourses by several organizations or actors related to the country’s history. These include schools, museums and non-governmental organizations such as the Persatuan Sejarah Malaysia (Malaysian Historical Society), The Patriots, the Pusat Sejarah Rakyat (People’s History Center) and the Kempen Sejarah Malaysia Sebenar (Real Malaysia History Campaign [KemSMS]). Using qualitative data, this study employs content analysis on each of their selected historical discourses. Apart from exploring their efforts at increasing historical awareness, this article maps out each actor’s inclination towards a set of historical information. Albeit that each of these actors strive to strengthen historical awareness within the community, the foundation of each discourse is different. Consequently, the essence of the historical awareness promoted becomes contradictory.